A Phase II Study of ERK Inhibition by Ulixertinib (BVD-523) in Metastatic Uveal Melanoma - Elizabeth I. Buchbinder; Justine V. Cohen; Giuseppe Tarantino; Christine G. Lian; David Liu; Rizwan Haq; F. Stephen Hodi; Donald P. Lawrence; Anita Giobbie‐Hurder; Deborah Knoerzer; Ryan J. Sullivan (2024)
Abstract Purpose: Uveal melanoma is a rare and aggressive subset of melanoma that is minimally responsive to traditional therapies. Greater than 80% of uveal melanomas have a mutation in GNAQ or GNA11 which lead to downstream signaling through the MAPK pathway. Ulixertinib (BVD-523) is a potent and reversible small-molecule ATP-competitive inhibitor of both ERK1 and ERK2 protein kinases. Materials and Methods: We performed a phase II study to determine the efficacy and safety of BVD-523 in patients with metastatic uveal melanoma. This was conducted as a Simon two-stage design with a sample size of 25 patients and an initial evaluation of efficacy after 13 patients. Results: From April 2018 to April 2019, 13 patients were enrolled. Patients were predominantly female (69%) with a median age of 64 years (34–76). Sites of metastases included liver (84.6%) and lung (30.8%). Grade 3 and 4 toxicities associated with therapy were consistent with ERK inhibitors and included liver function test (LFT) elevation, hyponatremia, pruritis, amylase elevation, anemia, and rash. The best response, per RECIST 1.1, was stable disease in 4 patients, and disease progression in 7 patients. Two patients were unevaluable for response due to withdrawal from study. Median time to progression was 2.0 months. There were eight deaths due to disease progression with a median overall survival of 6.9 months. Conclusions: ERK inhibition with ulixertinib (BVD-523) did not demonstrate activity in patients with metastatic uveal melanoma. The toxicities observed were consistent with what would be expected with MAPK pathway inhibition. Significance: Uveal melanoma is a difficult to treat disease with minimal therapy options. The majority of uveal melanomas have mutations in GNAQ or GNA11 leading to activation of the MAPK pathway. Efforts to target MEK in uveal melanoma has had mixed results. This phase II trial of ERK inhibition with BVD-523 examined the potential role of this agent in uveal melanoma therapy.